Passivation Behavior of Steel Rod and Wires of Nepal in Acidic and Alkaline Solutions - Bhattarai, Jagadeesh (Nepal Journal of Science and Technology, 2010)
The passivation behavior of steel rods and wires those are produced in Nepal was studied in 1 M HCl and 1 M NaOH solutions at 25°C, open to air using immersion tests and electrochemical measurements. The corrosion resistance of all the examined steel rods and wires in this work is found significantly higher in alkaline 1 M NaOH than in acidic 1 M HCl, mostly due to an ennoblement of the open circuit corrosion potentials of the steels at passive potential regions in 1 M NaOH solution at 25°C. The corrosion rate of all the examined steel rods and wires is about in the range of 1-5 x 101 mm/y in acidic 1 M HCl solution which is nearly three orders of magnitude lower corrosion resistance than in alkaline 1 M NaOH solution at 25°C. Therefore, these steel rods and wires seem to be very corrosion resistance materials in very alkaline environments like a reinforcing concrete. Key words: steels; corrosion rate; open circuit potential; immersion test; electrochemical measurements. DOI: 10.3126/njst.v9i0.3181 Nepal Journal of Science and Technology 9 (2008) 91-97